Optimization of bioengineered heparin/heparan sulfate production for therapeutic applications - Lord, Megan S. (Bioengineered, 2017)
Heparin has been used clinically as an anti-coagulant for more than 100 y and the major source of this therapeutic is still animal tissues. Contamination issues in some batches of heparin over 10 y ago have highlighted the need to develop alternative methods of production of this essential drug.(1) Bioengineering heparin by expressing serglycin in mammalian cells is a promising approach that was recently reported by the authors.(2) This addendum explores the approaches that the authors are taking to increase the yield of recombinantly expressed serglycin decorated with heparin/heparan sulfate focusing on cell culture and bioreactor conditions and proposes that the cell microenvironment is a key modulator of heparin biosynthesis.